Kepastian Hukum Jaminan Fidusia Pasca Putusan Mahkamah Konstitusi Nomor 2/Puu-Xix/2021 dalam Perspektif Globalisasi Ekonomi: Studi Perbandingan dengan Inggris dan Afrika Selatan - Bambang Wahyono; nuzula Sari; Yusuf Adiwibowo (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Constitutional Court Decision No.2/PUU-XIX/2021 limits the unilateral enforcement of fiduciary guarantees by requiring a judicial process if the debtor objects to a breach of contract. This study aims to analyze the legal certainty of fiduciary guarantees after the ruling from the perspective of economic globalization through a comparative study with the United Kingdom and South Africa. The research method used is normative law with statutory, conceptual, and comparative approaches. The results show that Indonesia has shifted from an execution model to judicial execution. The United Kingdom and South Africa continue to maintain unilateral execution with more measurable debtor protection mechanisms. This study recommends the reconstruction of Article 15 of the Fiduciary Guarantee Law to balance legal certainty, economic efficiency, and debtor protection.